TUTURAN DEKLARATIF DALAM BAHASA SMS MAHASISWA UNRI PRODI TEKNOLOGI HASIL PERTANIAN TAHUN 2015 - Yani, Juli; Rismayeti, Rismayeti; Hermansyah, Hermansyah (Universitas Lancang Kuning, 2017)
Traditionally, utterances are speech units used in a language directly. It contains series of words and complete thought. The utterances are used in various contexts. One of them is in SMS ( Short Messege Service ). SMS is a facility to send and receive short text messege via wireless device namely telephone mobile communication devices. In this case, the communication device used in cellular telephone. Related to that, this writing presents the analysis of declarative narratives used by students of Agriculture department in Riau University in 2015. It analyzes how the narratives are used and their meanings. Thus, the purpose of the analysis is to identify and describe the meaning of specch utterances of those students.